Influence of Thermal Annealing on PCDTBT:PCBM Composition Profiles. Issue 5 (11th November 2013) - Synooka, Olesia; Eberhardt, Kai‐Rudi; Singh, Chetan Raj; Hermann, Felix; Ecke, Gernot; Ecker, Bernhard; von Hauff, Elizabeth; Gobsch, Gerhard; Hoppe, Harald
<x xml:space="preserve">Abstract</x> A variety of measurement techniques including photothermal deflection spectroscopy (PDS), auger electron spectroscopy (AES), (sub–bandgap) external quantum efficiency (EQE), and impedance spectroscopy are applied to poly[N‐900‐hepta‐decanyl‐2, 7‐carbazole‐alt‐5, 5‐(40, 70‐di‐2‐thienyl‐20, 10, 30‐benzothiadiazole (PCDTBT)/[6, 6]‐phenyl C71 butyric acid methyl ester (PC71BM) films and devices to probe the stability under thermal annealing. Upon annealing, solar cell performance is drastically decreased for temperatures higher than 140 °C. Detailed investigation indicate changes in polymer:fullerene interactions resulting in the formation of a polymer wetting layer upon annealing at temperatures higher than 140 °C. Upon device completion this wetting layer is located close to the metal electrode and therefore leads to an increase in recombination and a decrease in charge carrier extraction, providing an explanation for the reduced fill factor (FF) and power conversion efficiency (PCE).